Energy optimization and low-carbon development of prefabricated buildings enabled by BIM technology - Wang Yuhong; Li Xiaoqin (Science and Technology for Energy Transition)
Against the backdrop of the global energy crisis and climate change, prefabricated buildings, with their high efficiency, energy saving and environmental protection, have become an important direction for the transformation and upgrading of the construction industry. However, despite the promising prospects of Building Information Modeling (BIM) technology and prefabricated buildings in the industry, prefabricated buildings still face many challenges in practical applications, especially in terms of energy efficiency, carbon emission control, and renewable energy integration, which urgently need further optimization. There are still many challenges in the actual application process, and the impact of factors such as government regulatory mechanisms, technical standard formulation, and talent training on the high-quality development of the prefabricated building industry cannot be ignored. Therefore, through literature research, model construction and case analysis, this paper explores the integrated application of BIM and energy management technology in prefabricated buildings, proposes a high-quality development evaluation model based on the Analytical Hierarchy Process (AHP)-fuzzy comprehensive evaluation method, and verifies the effectiveness of the model through the case of prefabricated building projects in Chengdu. The research results show that BIM technology plays an important role in improving the energy efficiency and low-carbon performance of prefabricated buildings. Through the analysis of prefabricated building projects in Chengdu, the feasibility of the model is verified, and strategic measures based on energy optimization are further proposed to promote the prefabricated building industry based on BIM technology to develop in a high-quality, low-carbon, and sustainable direction.